Effect of the carbon emissions trading policy on the co-benefits of carbon emissions reduction and air pollution control - Dong, Zhaoyingzi; Xia, Chuyu; Fang, Kai; Zhang, Weiwen (Energy policy, 2022)
Achieving the co-benefits of carbon emissions reduction and air pollution control is significant for pursuing a sustainable and low-carbon economy in China. This study applies the difference-in-differences method to explore the local and spillover impact of the carbon emissions trading policy (2011) on China's carbon emissions and air quality, based on city-level data. The results show that the carbon emissions trading policy significantly affects the co-benefits of the total carbon emissions reduction and air quality improvement. In addition to this direct effect, the carbon emissions trading policy could indirectly affect carbon emissions and air quality by changing the innovation ability of cities and location choice of local industries. Though the policy does not significantly affect the overall carbon emissions intensity in China, it is seen to be effective for Central China. Our further spatial analysis indicates that the policy increases the carbon emissions in neighboring cities, which supports the “pollution haven hypothesis.” Thus, this study contributes to the existing climate policy literature and provides a more comprehensive picture of the policy effect by integrating the co-benefits of the carbon emissions reduction and air pollution control, estimating both local and spillover effects and exploring the underlying mechanisms. •Influence of the 2011 carbon emissions trade policy in China is analyzed.•The policy indirectly affects total carbon emissions and air quality.•The policy does not significantly affect emissions intensity overall.•The policy pushes up emissions in neighboring cities.•The policy supports pollution haven hypothesis.